A novel coronavirus and a broad range of viruses in Kenyan cave bats - Kamau, J.; Ergunay, K.; Webala, P.W.; Justi, S.A.; Bourke, B.P.; Kamau, M.W.; Hassell, James M.; Chege, M.N.; Mwaura, D.K.; Simiyu, C.; Kibiwot, S.; Onyuok, S.; et al. (MDPI, 2022)
Background and Methods: To investigate virus diversity in hot zones of probable pathogen spillover, 54 oral-fecal swabs were processed from five bat species collected from three cave systems in Kenya, using metagenome sequencing. Results: Viruses belonging to the Astroviridae, Circoviridae, Coronaviridae, Dicistroviridae, Herpesviridae and Retroviridae were detected, with unclassified viruses. Retroviral sequences were prevalent; 74.1% of all samples were positive, with distinct correlations between virus, site and host bat species. Detected retroviruses comprised Myotis myotis, Myotis ricketti, Myotis daubentonii and Galidia endogenous retroviruses, murine leukemia virus-related virus and Rhinolophus ferrumequinum retrovirus (RFRV). A near-complete genome of a local RFRV strain with identical genome organization and 2.8% nucleotide divergence from the prototype isolate was characterized. Bat coronavirus sequences were detected with a prevalence of 24.1%, where analyses on the ORF1ab region revealed a novel alphacoronavirus lineage. Astrovirus sequences were detected in 25.9%of all samples, with considerable diversity. In 9.2% of the samples, other viruses including Actinidia yellowing virus 2, bat betaherpesvirus, Bole tick virus 4, Cyclovirus and Rhopalosiphum padi virus were identified. Conclusions: Further monitoring of bats across Kenya is essential to facilitate early recognition of possibly emergent zoonotic viruses.